2010
DOI: 10.1007/s11897-010-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Failure With Low Cardiac Output: Can We Develop a Short-term Inotropic Agent That Does Not Increase Adverse Events?

Abstract: Acute heart failure represents an increasingly common cause of hospitalization, and may require the use of inotropic drugs in patients with low cardiac output and evidence of organ hypoperfusion. However, currently available therapies may have deleterious effects and increase mortality. An ideal inotropic drug should restore effective tissue perfusion by enhancing myocardial contractility without causing adverse effects. Such a drug is not available yet. New agents with different biological targets are under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…27 In most patients with cardiac decompensation and low perfusion, the depressed cardiac function is a consequence of impaired myocardial contractility coupled with abnormal preload and afterload conditions. 28 Compensatory mechanisms triggered to restore contractility following a primary event of myocardial infarction or cardiomyopathy result in a downward spiral of worsening preload and afterload conditions, myocardial injury, and further decrease in contractility, culminating in a low cardiac output and impaired organ perfusion. 28 Prior studies have demonstrated the acute relationship of S1 amplitude with LV dP/dt max as a surrogate for LV contractility.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…27 In most patients with cardiac decompensation and low perfusion, the depressed cardiac function is a consequence of impaired myocardial contractility coupled with abnormal preload and afterload conditions. 28 Compensatory mechanisms triggered to restore contractility following a primary event of myocardial infarction or cardiomyopathy result in a downward spiral of worsening preload and afterload conditions, myocardial injury, and further decrease in contractility, culminating in a low cardiac output and impaired organ perfusion. 28 Prior studies have demonstrated the acute relationship of S1 amplitude with LV dP/dt max as a surrogate for LV contractility.…”
Section: Figurementioning
confidence: 99%
“…28 Compensatory mechanisms triggered to restore contractility following a primary event of myocardial infarction or cardiomyopathy result in a downward spiral of worsening preload and afterload conditions, myocardial injury, and further decrease in contractility, culminating in a low cardiac output and impaired organ perfusion. 28 Prior studies have demonstrated the acute relationship of S1 amplitude with LV dP/dt max as a surrogate for LV contractility. 11 Our study suggests that the haemodynamic association is preserved in spite of the unconventional sensor location and the use of accelerometer embedded within an implanted cardiac device to measure HSs.…”
Section: Figurementioning
confidence: 99%
“…75,76 A better understanding of its mode of action might help to reposition this drug in therapeutic regimens. Decades of intensive research have not yet solved the enigma surrounding the exact mechanism of action.…”
Section: Resultsmentioning
confidence: 99%
“…The ideal inotropic agent (1) should enhance cardiac pumping selectively without altering other parameters of cardiac function, (2) should not increase substantially cardiac energy consumption, and (3) should not increase the incidence of cardiac arrhythmias [16]. Since these requirements can hardly be met with interactions upstream to the contractile machinery, the downstream steps came into the focus of the research.…”
Section: Concept Of Myosin Activation: Ome-camtiv Mecarbil and Its Mementioning
confidence: 99%